Baishouwu Extract Suppresses the Development of Hepatocellular Carcinoma via TLR4/MyD88/NF-κB Pathway - Ding, Yong-fang; Peng, Zi-xuan; Ding, Lan; Peng, Yun-ru (Frontiers in Pharmacology, 2019)
Purpose The root of Cynanchum auriculatum Royle ex Wight, known as Baishouwu, has been widely used for a tonic supplement since ancient times. The current study was performed to explore the effect of Baishouwu on the development of experimental hepatocellular carcinoma (HCC) and the potential mechanism involved. Methods Rats were injected diethylnitrosamine (DEN) to initiate the multistep hepatocarcinogenesis. Animals were treated concurrently with Baishouwu given daily by oral gavage for 20 weeks to evaluate its protective effects. Time series sera and organ samples from each group were collected to evaluate the effect of Baishouwu on hepatic carcinogenesis. Results It was found that Baishouwu treatment successfully attenuated liver injury induced by DEN, as shown by decreased levels of serum biochemical indicators (AST, ALT, ALP, TP, T-BIL). Administration of Baishouwu inhibited the fibrosis-related index in serum and live tissue respectively from inflammation stage to HCC stage after DEN treatment. It significantly reduced the incidence and multiplicity of DEN-induced HCC development in a dose-dependent manner. Macroscopic and microscopic features suggested that treatment with Baishouwu for 20 weeks was effective in inhibiting DEN-induced inflammation, liver fibrosis and HCC. Furthermore, TLR4 overexpression induced by DEN was decreased by Baishouwu, leading to the markedly down-regulated levels of MyD88, TRAF6, NF-κB p65, TGF-β1 and α-SMA in hepatitis, cirrhosis and hepatocarcinoma. Conclusions In conclusion, Baishouwu exhibited potent effect on the development of HCC by altering TLR4/MyD88/ NF-κB signaling pathway in the sequence of hepatic inflammation-fibrosis-cancer, which provided novel insights into the mechanism of Baishouwu as a candidate for the treatment of HCC in the future.